Reflection of Cultural Crisis in Bhutanese Nepali Diasporic Poetry - Timalsina, Ramji (Researcher: A Research Journal of Culture and Society, 2020)
This article has discussed how Bhutanese Nepali diasporic poetry has depicted cultural crises of the community settled in Europe, America and Oceania. Twenty one poems composed by Bhutanese Nepali diasporic poets from 2009 to 2019 have been selected through purposive sampling and their content analysis has been conducted with the focus on their themes. The study has found that the Bhutanese Nepali culture has been in crisis in the diaspora. The community is working to preserve it; but many socio-economic conditions do not favour them. They find problems in celebrating their festivals, eating their food, observing the rituals, using language, wearing traditional Nepali dress, and following their work pattern. With these difficulties and being in the minority marginal position in the host land, they find their identity in crisis resulting into emotional insecurity. It is believed that this article will contribute to the study of diasporic culture and the problems of the transnational migrant communities.